ANALYZE THE STANDARD OF PHARMACY PRACTICE APPLICATION IN PHARMACY COMMUNITY AT YOGYAKARTA CITY - Kuswardani Dwi Atmini; Ibnu Gholib Gandjar; Achmad Purnomo (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
In increasing social health services there are a lot of effort that have been done by the government such as providing facilities of health services such as pharmacy. As an effort to make phamacist can give a profesional pharmacy practice based on the decision of Health Minister Republic of Indonesia No.27/Menkes/SK/IX/2004 about the Standard of Pharmacy Practice in pharmacy community the goal is to find out the figure of Standards of Pharmacy Practice implementation in pharmac community at Yogyakarta City. The results of the research generally showed that the standards of pharmacy practice in Yogyakarta has not been implemented well. Total score for the standards pharmacy practice based on pharmacists respondent 21% (good), 79% (enough); employees respondent 21% (good), 75% (enough), 4% (bad) and patients respondent 38% (good), 42% (enough), 20% (bad). The inhibiting factors towards the implementation standards of pharmacy practice such as education programme, seminar or another thing that rarely held that make the opportunity for self development very limit, the socialization are rare and control function from institution that have authority are weak so monitoring and evaluation should do periodicaly. Keywords : Standards of Pharmacy Practice, Pharmacy, Pharmacist, Employees, Patients